Two new species of Foa (Apogonidae) from the Pacific Plate, with redescriptions of Foa brachygramma and Foa fo - Fraser, Thomas H.; Randall, John E. (Zootaxa, 2011)
Species of the Indo-Pacific apogonid fish genus Foa known from the Pacific Plate are reviewed. The type species of Foa, F. brachygramma, is redescribed including information on the distribution of lateralis canal pores and free neuromasts on the head, body and caudal fin. This species, formerly ascribed as having a wide Indo-Pacific distribution, is restricted to the Hawaiian Islands. Foa fo, type locality Philippines, with an apparent Indo-Pacific distribution (but not the Hawaiian Islands), has 12–15 gill rakers (14–16 for F. brachygramma), and four or five irregular dark bars and whitish spots on the head and body (F. brachygramma has dark edging on the scales and lacks whitish spots). A lectotype from the Philippines is selected for Foa fo. Foa leisi is described as a new species from French Polynesia, olivaceous with three faint brown bars on body, one under each dorsal fin and on anterior on caudal peduncle; head and anterior body with dark-edged whitish spots. Foa nivosa is described as new species from Palau, Marshall Islands and Fiji, pale yellowish tan with numerous red-edged whitish spots, smaller on head. The axial skeletons are compared for Foa brachygramma, F. fo, F. hyalina, F. leisi, and F. nivosa. Foa madagascariensis and its synonym Apogonichthys zuluensis are not treated here, but Petit’s species is recognized as valid. The following characters can be used to identify species: color patterns, pored lateral-line scales as they vary with standard length, number of gill rakers and rudiments, mandibular pore and certain free neuromast patterns.